2013
DOI: 10.7314/apjcp.2013.14.5.2865
|View full text |Cite
|
Sign up to set email alerts
|

The KIF1B (rs17401966) Single Nucleotide Polymorphism is not Associated with the Development of HBV-related Hepatocellular Carcinoma in Thai Patients

Abstract: Hepatitis B virus (HBV) infection can become chronic and if left untreated can progress to hepatocellular carcinoma (HCC).Thailand is endemic for HBV and HCC is one of the top five cancers, causing deaths among Thai HBV-infected males. A single nucleotide polymorphism (SNP) at the KIF1B gene locus, rs17401966, has been shown to be strongly associated with the development of HBV-related HCC. However, there are no Thai data on genotypic distribution and allele frequencies of rs17401966. Thai HBV patients seropos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Therefore, it is important to evaluate the role of KIF1B rs17401966 in the genetic susceptibility to HCC and gene-environment interactions. Interestingly, three studies found that KIF1B rs17401966 was not associated with the development of HBV-related HCC in Thai, Japanese, and Saudi Arabian patients[85-87], and two other studies identified that KIF1B rs17401966 exerted protective effects against the susceptibility to HBV-related HCC in Chinese patients[88,89]. These inconsistencies might partly be because different ethnicities or study populations have distinct genetic architectures.…”
Section: Snpsmentioning
confidence: 99%
“…Therefore, it is important to evaluate the role of KIF1B rs17401966 in the genetic susceptibility to HCC and gene-environment interactions. Interestingly, three studies found that KIF1B rs17401966 was not associated with the development of HBV-related HCC in Thai, Japanese, and Saudi Arabian patients[85-87], and two other studies identified that KIF1B rs17401966 exerted protective effects against the susceptibility to HBV-related HCC in Chinese patients[88,89]. These inconsistencies might partly be because different ethnicities or study populations have distinct genetic architectures.…”
Section: Snpsmentioning
confidence: 99%
“…Genomic DNA was extracted from 100 µl peripheral blood mononuclear cells (PBMCs) using phenolchloroform-isoamyl alcohol isolation method as described previously (Sopipong et al, 2013). The quality of DNA was measured using spectrophotometer (NanoDrop 2000c, Thermo Scientific).…”
Section: Dna Preparation and Genetic Analysismentioning
confidence: 99%
“…This might be explained by differences in the genetic diversity among Japanese, Korean, and Chinese populations or by multiple causative factors of hepatocarcinogenesis such as age, gender, environmental toxins, alcohol intake, HBV viral load, genotype, and distinct mutations. Other groups have also showed no association between the KIF1B variants and HBV‐related HCC in replication studies in Saudi Arabian and Thai ethnicities [Al‐Qahtani et al, ; Sopipong et al, ]. On the other hand, the KIF1B variants were not associated with susceptibility to chronic HBV infection in Chinese population, implying distinct genetic susceptibility factors might contribute to the progression from HBV infection to HCC [Zhong et al, ].…”
Section: Hepatocarcinogenesismentioning
confidence: 99%